TENUNAN SONGKET MELAYU RIAU DI KOTA DUMAI PROVINSI RIAU - sari, Mutia; Efi, Agusti; Adriani, Adriani (Journal of Home Economics and Tourism, 2015)
Riau Malay songket woven in Dumai City is a traditional cloth Melayu Riau Riau Malay cultural heritage. Current issues Malay songket weaving is not widely known outside the community of Riau, this study aimed to describe the Riau Malay songket woven In Kota Dumai which includes the type of thread, color, dye and dyeing yarnThe method used is descriptive qualitative method. Collecting data in this study is done by using observation, interviews and documentation. Source of data taken is shaped notes both written and non-written (recorded) derived from informants who were interviewed, documentation, literature study. Furthermore, the data reviewed and analyzed by the steps of data reduction, data presentation, drawing conclusions. Data validation was done with the extension of observation, increase persistence and triangulation.The results showed that the type of thread used to weave songket in Kota Dumai Riau Malay is cotton yarn (CSM) with an assortment of colors, embroidery thread and gold thread for motives. Riau Malay songket woven color in Dumai city which initially predominantly use original colors (red, yellow, green) has developed into unlimited colors, so that the use of color today are very diverse. Dyes used for dyeing yarn dye is artificial (synthetic). Substances in the form of powder or powder color is called dye procion. Natural dye is not used as a reason for the creation of a long natural dyes and natural dye material limitations that exist. The process of yarn dyeing yarn bleaching done in advance, after the bleached yarn dyeing yarn made into a synthetic dye..Keyword: Songket, Melayu, Dumai